NEGARA DAN MASYARAKAT DALAM RESOLUSI KONFLIK DI INDONESIA (Daerah Konflik Kalimantan Barat dan Kalimantan Tengah) - Heru Cahyono (Jurnal Penelitian Politik, 2007)
An explosion ofethnic conflicts in West Kalimantan 1999 andCentral Kalimantan 2001 shook the entire area Media reports ofwidespread violence often including beheadings cannibalism and ethnic cleansing In both case a single ethnic group migrants from the island of Madura was targeted and accounted for the overwhelming majority of victims State have a little role to push conflict resolution Jakarta s tardy response read clearly in both cases especially in Central Kalimantan We very shockly how can violence killed hundreds ofpeople The state s response to mass murders killed has been too little and too late National intervention is usually required But because the state lacks an national rapid response force and because state has so far been either paralyzed or unwilling to act mass killing has gone unchecked The Madurese in West and Central Kalimantan were particularly hard hit by these conflicts Most had to abandon their homes and livelihoods and seek shelter in safe areas in the Kalimantan orfarther away in Madura Recently most internally displacedpersons IDPs from the 2001 Central Kalimantan conflict have begun returning however IDPs from the West Kalimantan district ofSambas who fled during the 1999 conflict have been barred from returning to their homes Locals and returnees note an increased on physical intimidation an unwelcome situation and a general sense ofinsecurity Although years have passed since the conflicts erupted resolution is still elusive for many people The peace process in Sambas West Kalimantan still stagnant and should be re launched to enable the return ofIDPs.